Application of numerical analysis in geotechnical engineering practice - Zdravkovi,L; Potts,DM (2010)
Numerical analysis, in the form of the finite element, finite difference or boundary element method, has become a preferred calculation tool in the design of complex geotechnical structures. Even new codes of practice, such as the European EUROCODE 7, encourage the use of numerical analysis in design. However, as there is no general guidance and agreement in the international community on appropriate numerical solvers, constitutive models and boundary conditions, there are often examples of bad practice in the numerical analysis of geotechnical structures. Through examples of the analyses of real problems, this paper investigates the use of appropriate constitutive models and boundary conditions, to highlight both the successful use and the potential pitfalls of modern numerical analysis. © 2010 ASCE.